Ligan SV2A sebagai Terapi Epilepsi - Novianae, Lindae; Sumarno, Sumarno (Jurnal Farmasi Udayana; Vol. 9, No. 1, Tahun 2020DO - 10.24843/JFU.2020.v09.i01.p01, 2020)
Epilepsi described a condition in which a person has recurrent seizures due to a chronic, underlying process. Seizure is a transient occurrence of sign or symptoms due to abnormal excessive or synchronous neuronal activity in the brain. Seizure are a result of a shift in the normal balance of excitation and inhibition within the CNS. The ILAE has released a 2017 version of seizure-type classification, basic and expanded version. Seizure classification is an important element in designing the treatment plan, because some epileptic drugs have different activities against various seizure types. Antiepileptic drugs to act primaryli by blocking the initiation or spread of seizures through a variety of mechanism. The newer mechanism of antiepileptic drugs is binding to the glycoprotein SV2A. This paper discuss SV2A ligand Levetiracetam and brivaracetam for the treatment of epilepsy. Discussed include aspect pharmacology, some clinical studies about efficasy, safety, and tolerability, so it can provide information related to the new drug SV2A ligand in determining drug choices for the treatment of epilepsy. Keywords: epilepsy, brivaracetam, levetiracetam, seizure, SV2A ligands